Aluminum-scandium-nitrogen ferroelectric capacitance memory based on nitride bottom electrode and preparation method thereof
By growing metal nitride bottom electrodes in a nitrogen-rich environment, modulating the grain size and grain boundary number of the AlScN ferroelectric layer, the nitrogen vacancy and oxidation problems in the AlScN ferroelectric capacitor memory are solved, and lower leakage, coercive electric field, higher breakdown electric field and high temperature stability are achieved.
Patent Information
- Application Number
- CN202411768952.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-18
AI Technical Summary
The existing AlScN ferroelectric capacitor memory has problems such as nitrogen vacancy, oxidation problems, high coercive electric field, and large leakage, which affects its performance and life.
The performance regulation method of aluminum scandium nitrogen ferroelectric capacitor memory based on nitride bottom electrode is adopted. By growing metal nitride bottom electrodes in a nitrogen-rich environment, the grain size and grain boundary number of the AlScN ferroelectric layer are modulated to reduce nitrogen vacancy and oxidation.
Effectively reduce leakage, reduce coercive electric field, improve breakdown electric field, and improve the high temperature stability and residual polarization value of AlScN-based ferroelectric capacitors.
Smart Images

Figure CN119653784A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ferroelectric memory, and in particular relates to a method for controlling the performance of an aluminum-scandium-nitrogen ferroelectric capacitor memory based on a nitride bottom electrode. Background Art
[0002] Aluminum scandium nitride (AlScN) is a new type of ferroelectric material with a conductivity greater than 130μC / cm 2 The residual polarization value P r , the device can be miniaturized to less than 10nm, is compatible with CMOS technology and has strong high-temperature stability, which makes AlScN-based ferroelectric capacitor memory devices have great application potential. Most of the existing AlScN ferroelectric capacitor MFM bottom electrodes are based on metal electrodes (Pt, Mo, Al, etc.) and semiconductor electrodes (Si, GaN, AlGaN, etc.). However, AlScN ferroelectric capacitor memory based on this type of bottom electrode material still has certain defects, mainly manifested in:
[0003] 1. After the scandium (Sc) element is doped into aluminum nitride (AlN), Sc replaces some Al atoms to form bonds with N. In this substitution process, non-ideal nitrogen vacancies will be generated. Nitrogen vacancies, as a donor-like defect, will lead to increased leakage. AlScN doped with low Sc content (<30%) has an extremely high coercive electric field E C And a lower breakdown electric field to coercive field ratio E BD / E C , which causes AlScN-based ferroelectric capacitors to operate in the "dangerous zone", which has a serious impact on their lifespan. At the same time, a higher coercive field means higher power consumption and higher heat generation. While AlScN doped with a high Sc content (>30%) reduces the coercive field to a certain extent, a higher Sc doping content will result in a residual polarization value P r Rapid decrease (<70μC / cm 2 ), and at the same time, more substitutional defects will be introduced into the AlScN body, resulting in increased device leakage and reduced lifespan.
[0004] 2. Due to the limitation of AlScN itself, during the growth of AlScN, the residual oxygen in the chamber and the adsorbed oxygen of the bottom electrode (the main factor) can easily diffuse into the AlScN body along the grain boundary of AlScN to fill the nitrogen vacancies and form Al-O and Sc-O bonds. These non-ideal bonds will further inhibit the bonding of Al-N and Sc-N, resulting in poor crystal quality of AlScN, increased device leakage, and reduced breakdown electric field. At the same time, the non-ideal bonding of Al-O and Sc-O at the AlScN grain boundary will lead to AlScN domain pinning, which will lead to incomplete polarization reversal and residual polarization P r Sharply decreased.
[0005] 3. AlScN is a "single crystal-like" material. Larger grain size and fewer grain boundaries are one of the ways to achieve low leakage and low coercive electric field. At the same time, inhibiting the oxidation of Al and Sc in the AlScN body can further reduce the leakage of the device. The AlScN ferroelectric layer will continue to grow along the grain boundaries of the bottom electrode seed layer. Traditional metal electrodes are difficult to use as seed layers to promote AlScN to form larger grain sizes due to their smaller grain size and more grain boundaries, which hinders the further improvement of the performance of AlScN memory devices. Summary of the invention
[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a method for controlling the performance of aluminum-scandium-nitrogen ferroelectric capacitor memory based on a nitride bottom electrode to solve at least one of the following problems: the problem of nitrogen vacancies when AlScN thin film is doped with Sc; the problem that Al and Sc elements in AlScN itself are easily oxidized; the low Sc-doped AlScN-based ferroelectric capacitor has a large coercive field and a low breakdown electric field to coercive field ratio E BD / E C and large leakage current, and it is expected to achieve at least one of the following effects: reduce leakage current, reduce coercive electric field E C , increase the breakdown electric field E BD , improving the high temperature stability of AlScN-based ferroelectric capacitors.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] Aluminum-scandium-nitride ferroelectric capacitor memory based on nitride bottom electrode, the bottom electrode of the aluminum-scandium-nitride ferroelectric capacitor memory is a nitride bottom electrode.
[0009] In one embodiment, the AlScN ferroelectric capacitor memory is composed of a substrate, a nitride bottom electrode, an AlScN ferroelectric layer and a metal top electrode in order from bottom to top.
[0010] In one embodiment, the substrate is a heavily doped P-Si substrate, and the AlScN ferroelectric layer is Al 1-x Sc x N, 0.1≤x≤0.3.
[0011] In one embodiment, the nitride bottom electrode is one of TiN, TaN, MoN, AgN, and WN.
[0012] The present invention also provides a method for preparing the aluminum-scandium-nitrogen ferroelectric capacitor memory based on a nitride bottom electrode, by growing a metal nitride electrode as the bottom electrode of the aluminum-scandium-nitrogen ferroelectric layer in a nitrogen-rich environment to achieve performance control of the aluminum-scandium-nitrogen ferroelectric capacitor memory, the preparation method comprising the following steps:
[0013] Step 1, pre-treating the substrate;
[0014] Step 2, depositing the nitride bottom electrode on the substrate in a nitrogen-rich environment, wherein the nitrogen-rich environment refers to a sputtering gas composed of nitrogen and argon with a flow ratio of 0.55 to 0.64;
[0015] Step 3, depositing an AlScN ferroelectric layer on the nitride bottom electrode;
[0016] Step 4: depositing a metal top electrode on the AlScN ferroelectric layer and processing the metal top electrode pattern.
[0017] In one embodiment, the step 1, pre-treating the substrate includes cleaning and oxide removal, and the process is as follows:
[0018] Step 1.1, using acetone, isopropanol, deionized water and ethanol to clean in sequence to remove impurities on the substrate surface;
[0019] Step 1.2, using BOE solvent to remove oxides on the surface of the substrate at room temperature, and then using deionized water to remove residual BOE on the surface; the BOE solvent is a mixture of HF aqueous solution and NH4F aqueous solution.
[0020] In one embodiment, the step 2 is to deposit the nitride bottom electrode on the substrate, and the process is as follows:
[0021] Step 2.1, fixing the substrate;
[0022] Step 2.2, using a metal target as a sputtering target and argon and nitrogen as sputtering gases, pre-sputtering the target to remove oxides on the surface of the target;
[0023] Step 2.3, formal sputtering at room temperature.
[0024] In one embodiment, in step 2.2, the RF sputtering power is 400-500W, the argon flow rate is 45-55sccm, the nitrogen flow rate is 25-35sccm, and the flow ratio of nitrogen to argon is 0.55-0.64. Under the flow ratio of nitrogen to argon of the present invention, the nitride seed layer and the AlScN ferroelectric layer can achieve a larger grain size, a smaller number of grain boundaries, and a lower surface roughness.
[0025] In one embodiment, the step 3, depositing an AlScN ferroelectric layer on the nitride bottom electrode, is performed as follows:
[0026] Step 3.1, using the ScAl alloy target as the sputtering target, argon and nitrogen as the sputtering gas, pre-sputtering the target to remove the oxide on the surface of the target; wherein the RF sputtering power is 5-30kW, the flow rates of argon and nitrogen are 70-100sccm and 14-20sccm respectively, and the flow ratio of argon to nitrogen is 5:1;
[0027] Step 3.2, formal sputtering at 100-300°C.
[0028] In one embodiment, in step 4, a metal top electrode is deposited on the AlScN ferroelectric layer, and the process is as follows:
[0029] Step 4.1, using a metal target as a sputtering target, argon and nitrogen as sputtering gases, pre-sputtering the target to remove oxides on the target surface, wherein the RF sputtering power is 400-500W;
[0030] Step 4.2, formal sputtering at room temperature.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. During the high-temperature growth of AlScN film, some nitrogen atoms in the metal nitride bottom electrode will diffuse into the AlScN film to fill nitrogen vacancies, thereby improving the leakage of the AlScN ferroelectric capacitor.
[0033] 2. The process of growing metal nitride bottom electrode in a nitrogen-rich environment inhibits oxygen adsorption on the surface of the nitride electrode, improves the oxidation of the AlScN film, improves the crystal quality of the AlScN film, and increases the residual polarization P r , improve the leakage situation.
[0034] 3. Grow the metal nitride bottom electrode seed layer in a nitrogen-rich environment, modulate the nitride electrode grain size and grain boundary quantity, and then modulate the AlScN ferroelectric layer to produce a larger grain size and fewer grain boundaries. r (>140μC / cm 2 ) based on the further reduction of the coercive electric field E C and increase the breakdown electric field E BD .
[0035] 4. The metal nitride electrode does not form a thick reaction layer at the interface with AlScN and can prevent the formation of nitrogen defects at the interface, thereby improving the degradation of memory reliability and other properties required for the application.
[0036] 5. The metal nitride electrode has high temperature stability. The process of growing the metal nitride bottom electrode in a nitrogen-rich environment can further improve the high temperature stability of the AlScN-based ferroelectric capacitor.
[0037] 6. The miniaturization and easy processing of metal nitride electrodes. In high storage density memory applications, the integration of metal nitride electrodes and AlScN films is conducive to micromachining (compatible with CMOS process) and cost reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic diagram of the structure of the AlScN ferroelectric capacitor memory device of the present invention.
[0039] Figure 2 It is a process flow chart of preparing AlScN ferroelectric capacitor based on nitride electrode seed layer of the present invention.
[0040] Figure 3 The experimental result data of step 2 of the present invention is that the argon flow rate is 50sccm, and the nitrogen flow rates are 3sccm, 7sccm, 10sccm, and 30sccm respectively. Among them, (a) is the PV circuit measured at 100kHz for the nitride bottom electrode deposited under different nitrogen environments. (b) is the statistical analysis of the change of 2Pr with N2 flow rate (20 devices are measured in each group). (c) is the JV curve. (d) is the statistical analysis of the change of current density J with N2 flow rate (20 devices are measured in each group). (e) is the relationship between the number of cycles before breakdown of all samples and 2Pr. (f) is E BD / E C Statistical analysis of the changes with N2 flow rate (10 devices measured in each group).
[0041] Figure 4 It is a schematic diagram of the effect of the crystallization characteristics of the nitride electrode of the present invention on the crystallization of the AlScN ferroelectric layer.
[0042] Figure 5 These are the AFM and TEM characterization results, where (a) is a nitride electrode grown in a low-nitrogen environment, and (b) is a nitride electrode grown in a nitrogen-rich environment. In (a) and (b), the upper figure is the AFM characterization result, and the lower figure is the TEM characterization result.
[0043] Figure 6 This is a schematic diagram of the diffusion of nitrogen in the nitride electrode into the AlScN body to promote Al / Sc-N bonding and inhibit oxidation reactions. DETAILED DESCRIPTION
[0044] The embodiments of the present invention are described in detail below with reference to the accompanying drawings and examples.
[0045] like Figure 1 As shown, the aluminum-scandium-nitrogen ferroelectric capacitor memory of the present invention adopts a nitride bottom electrode. Its specific structure mainly consists of a substrate, a nitride bottom electrode, an AlScN ferroelectric layer and a metal top electrode from bottom to top.
[0046] Further, in the present invention, the substrate is P + -Si, AlScN ferroelectric layer is Al 1-x Sc x N, wherein 0.1≤x≤0.3, at this content a higher residual polarization can be achieved, and more preferably x=0.2.
[0047] The nitride bottom electrode of the present invention may be one of TiN, TaN, MoN, AgN and WN.
[0048] The present invention controls the process parameters of the preparation process, that is, increases the nitrogen ratio during the growth of the nitride electrode, and can achieve the regulation of key properties such as coercive electric field, breakdown voltage, leakage current, and residual polarization in the low Sc-doped AlScN ferroelectric layer. Figure 2 As shown, the preparation method of the aluminum-scandium-nitrogen ferroelectric capacitor memory based on the nitride bottom electrode of the present invention mainly includes the following steps:
[0049] Step 1: pre-treat the substrate.
[0050] Specifically, P + -Si is used as the substrate, and its surface impurities are cleaned and oxides are removed. The main process is as follows:
[0051] Step 1.1, use acetone, isopropanol, deionized water and ethanol to clean in sequence to remove impurities on the surface of the p-Si substrate. The cleaning time is 5-10min, 3-5min, 1-3min, and 1-3min respectively. The cleaning is carried out in an ultrasonic device. After cleaning, a nitrogen gun is used to blow dry the surface. Isopropanol is used to remove residual acetone solvent, while deionized water is used to remove residual isopropanol solvent.
[0052] Step 1.2, using BOE solvent to remove oxides on the surface of the substrate at room temperature for 1-3 minutes, then using deionized water to remove residual BOE on the surface for 1-3 minutes, and using a nitrogen gun to blow dry the surface. The BOE solvent used in this embodiment is a mixture of a 49% by weight HF aqueous solution and a 40% by weight NH4F aqueous solution in a volume ratio of 1:7, which has a strong ability to remove oxides on the surface of the p-Si substrate.
[0053] Step 2, depositing a nitride bottom electrode on the substrate.
[0054] In this step, during the growth of the nitride bottom electrode seed layer, a specific sputtering power, a specific target material, a specific gas and gas flow rate, and a specific growth temperature are used to deposit the nitride bottom electrode. By modulating the growth process of the nitride bottom electrode seed layer, that is, changing the nitrogen ratio during the growth of the nitride electrode, and depositing in a nitrogen-rich environment, it is possible to achieve regulation of key characteristic parameters such as coercive electric field, breakdown voltage, leakage, and residual polarization in the low Sc-doped AlScN ferroelectric layer.
[0055] The nitrogen-rich environment of the present invention refers to increasing the flow rate of nitrogen gas introduced during the growth of the metal nitride electrode, and growing the metal nitride electrode in a nitrogen atmosphere with a higher concentration. The introduced nitrogen gas and argon gas have an optimal ratio, and the metal nitride electrode grown under this growth process parameter has better quality, and its conductivity will not decrease.
[0056] Step 2.1, fix the substrate. For example, high-purity silicone oil that is resistant to high temperatures and easy to clean is used to fix the substrate. + -Si substrate for fixing. High temperature resistant silicone oil IOTA-255A is a modified phenyl silicone oil with high phenyl content. It has better high temperature resistance than ordinary phenyl silicone oil and a wider working temperature range than ordinary phenyl silicone oil (-70℃~320℃). It is a modified phenyl silicone oil used for high and low temperature resistance.
[0057] Step 2.2, using high-purity Ti, Ta, Mo and other metal targets as sputtering targets, argon and nitrogen as sputtering gases, and setting the RF sputtering power to 400-500 W. Preferably, the argon flow rate is 45-55 sccm, and the nitrogen flow rate is 25-35 sccm.
[0058] Step 2.3, pre-sputter the target material before formal sputtering to remove oxides on the target surface. The pre-sputtering time is 10-20 minutes.
[0059] Step 2.4, formal sputtering at room temperature.
[0060] In this step, argon is used to bombard the metal target to separate the metal atoms, and then react with the nitrogen gas to form a nitride electrode. Preferably, the flow ratio of nitrogen to argon is 0.55 to 0.64. In the embodiment of the present invention, the argon flow rate is 50 sccm, and the nitrogen flow rates are 3 sccm, 7 sccm, 10 sccm, and 30 sccm, respectively. The experimental results are shown in Figure 2. Figure 3 As shown. It can be seen that the aluminum-scandium-nitrogen ferroelectric capacitor memory prepared based on the nitrogen-rich metal nitride bottom electrode has a remanent polarization P close to the theoretical value. r , minimum leakage, maximum E BD / E C , smaller coercive field E C And excellent uniformity.
[0061] In a nitrogen atmosphere of this concentration, the conductivity of the nitride electrode will not be reduced. By changing the ratio of nitrogen to argon, the grain size, number of grain boundaries and final surface roughness of the nitride seed layer and the AlScN ferroelectric layer are modulated. Specifically, the higher the nitrogen content, the larger the grain size, the fewer the number of grain boundaries and the lower the surface roughness of the nitride seed layer. The AlScN ferroelectric layer is then modulated to produce a larger grain size, a fewer number of grain boundaries and a lower surface roughness, such as Figure 4 The AFM and TEM test results are shown in Figure 5 As shown, it can be seen that the metal nitride electrode grown in the nitrogen-rich environment of the present invention has a larger grain size and a smaller number of grain boundaries. The nitrogen-rich environment inhibits oxygen adsorption on the surface of the metal nitride bottom electrode and improves the oxidation inside the AlScN film and at the interface. At the same time, the AlScN film will continue to grow along the grain boundaries of the metal nitride bottom electrode, and some nitrogen atoms in the metal nitride bottom electrode will diffuse into the AlScN film to fill nitrogen vacancies, repair the grain boundary defects of the AlScN film, reduce the number of grain boundaries in the AlScN film, and reduce leakage paths. As a result, the AlScN film achieves a larger grain size, a smaller number of grain boundaries, and a better surface flatness (smaller RMS), which improves the crystallization quality of the AlScN film.
[0062] In this step, the nitrogen-rich environment for growing nitride electrodes can modulate the nitrogen ratio in the nitride electrodes, inhibit the bonding between metal and O, reduce the oxidation of nitride itself, inhibit the adsorption of O on the nitride surface, and avoid the diffusion of O atoms along the grain boundaries into the AlScN body to fill nitrogen vacancies and form Al-O and Sc-O with Al and Sc during the subsequent high-temperature growth of AlScN. Figure 6 shown.
[0063] Furthermore, the excess nitrogen atoms in the nitride electrode will diffuse into the AlScN body to fill nitrogen vacancies (N vacancy) during the high-temperature AlScN growth process, inhibiting Al-O and Sc-O bonding (oxidation reaction), promoting Al-N and Sc-N bonding, merging grains to reduce the number of grain boundaries, and thus forming larger grain sizes. Figure 4 shown.
[0064] This step adopts the process of growing nitride (TiN, TaN, MoN, etc.) bottom electrode in a nitrogen-rich environment, which can increase the nitrogen element ratio of the nitride electrode. During the high-temperature growth of AlScN film, some N atoms in the nitride bottom electrode diffuse into the AlScN body to fill nitrogen vacancies, thereby improving the leakage of the AlScN ferroelectric capacitor and solving the nitrogen vacancy problem caused by Sc doping in the AlScN film.
[0065] This step adopts the bottom electrode process of growing nitride (TiN, TaN, MoN, etc.) in a nitrogen-rich environment, which can inhibit the oxygen adsorption and self-oxidation of the nitride surface, thereby achieving the purpose of inhibiting the oxidation reaction of the AlScN film, improving the crystal quality of the AlScN film, improving the residual polarization, improving the leakage situation, and solving the problem that the Al and Sc elements of AlScN itself are easily oxidized.
[0066] This step uses a nitrogen-rich environment to grow nitride (TiN, TaN, MoN, etc.) bottom electrode process. According to the characteristics that the growth mode of the nitride bottom electrode seed layer will continue to extend along the bottom electrode seed layer, the nitrogen-rich environment to grow the nitride bottom electrode seed layer can increase the nitride grain size and reduce the number of grain boundaries, thereby modulating the AlScN ferroelectric layer to achieve a larger grain size and fewer grain boundaries. On the basis of improving the residual polarization Pr of the AlScN-based ferroelectric capacitor, the leakage is further reduced and the coercive electric field E is reduced. C , increase the breakdown electric field E BD . This solves the problem that the low Sc-doped AlScN-based ferroelectric capacitor has a large coercive field and a low breakdown electric field to coercive field ratio E BD / E C And the problem of large leakage.
[0067] Nitride electrodes have high temperature stability, and the process of growing nitride bottom electrodes in a nitrogen-rich environment can further improve the high temperature stability of AlScN-based ferroelectric capacitors.
[0068] Step 3, depositing an AlScN ferroelectric layer on the nitride bottom electrode.
[0069] In this step, during the growth process of the AlScN ferroelectric layer, a specific sputtering power, a specific target material, a specific gas and gas flow rate, and a specific growth temperature are used to deposit the AlScN ferroelectric layer. The specific process is as follows:
[0070] Step 3.1, using ScAl alloy target as sputtering target, argon and nitrogen as sputtering gas, setting RF sputtering power to 10kW, argon and nitrogen flow rates to 85sccm and 17sccm respectively. Preferably, the ScAl target is a Sc0.2Al0.8 alloy target with 20% Sc content. The selection of this content can avoid the increase of AlScN body defects caused by incomplete substitution of high Sc content as much as possible, and at the same time achieve a larger residual polarization Pr. Combined with the nitride seed layer growth process of step 2, the growth modulation of the AlScN ferroelectric layer can be achieved.
[0071] Step 3.2, pre-sputter the target material before formal sputtering to remove oxides on the target surface. The pre-sputtering time is 10 minutes to 20 minutes.
[0072] Step 3.3, formal sputtering at 200°C.
[0073] Step 4: deposit a metal top electrode on the AlScN ferroelectric layer.
[0074] In this step, during the growth of the metal top electrode, a specific sputtering power, a specific target material, a specific gas and gas flow rate, and a specific growth temperature are used to deposit the metal top electrode. The specific process is as follows:
[0075] Step 4.1, use high-purity Pt, Mo, Al, Ti and other metal targets as sputtering targets, argon and nitrogen as sputtering gases, and set the RF sputtering power to 400-500W.
[0076] Step 4.2, pre-sputtering, is used to remove oxides on the surface of the target material. The pre-sputtering time is 10-20 minutes.
[0077] Step 4.3, formal sputtering at room temperature.
[0078] Step 5: Processing the metal top electrode pattern.
[0079] This step uses a specific photolithography process to form a top electrode pattern. The specific process is as follows:
[0080] Step 5.1, use AZ6130 photoresist and use the Leibo Spin Master 100 coating machine. Preferably, the coating speed is: acceleration 600r / 5s, uniform speed 4000r / 30s, forming a 3μm thick photoresist. AZ6130 photoresist is a positive photoresist with a thickness of 2.5-3μm, a resolution of 1.5μm, high temperature resistance, and is suitable for dry etching.
[0081] Step 5.2, after the photoresist is coated, a hot plate is used to pre-bake the photoresist to cure the photoresist. Preferably, the pre-bake temperature is 100° C. and the pre-bake time is 2 minutes.
[0082] Step 5.3, use MA6-1 photolithography machine for exposure, preferably, the exposure mode is HARD, and the exposure time is 3.8-4.5s.
[0083] Step 5.4, using 3038 solvent to develop the exposed epitaxial wafer for photoresist patterning, wherein the 3038 solvent is a positive photoresist developer, with a concentration of 2.380±0.01wt% of high-purity TMAH (tetramethylammonium hydroxide).
[0084] Step 5.5, using a hot plate to harden the patterned photoresist for further curing the photoresist to avoid denaturation of the photoresist during the metal dry etching process. Preferably, the curing temperature is 110° C. and the curing time is 120 s.
[0085] Step 6: forming a top electrode metal pattern.
[0086] This step uses a metal dry etching process to form a top electrode metal pattern
[0087] Step 6.1: Fix the sample and use high-purity silicone oil to fix the semiconductor device.
[0088] Step 6.2, use an IBE dry etcher to perform dry etching patterning on the metal top electrode. Preferably, in order to avoid the residual photoresist in the chamber from contaminating the device, use O2-Plasma to clear the chamber (no etching sample is placed during clearing). The O2 flow rate is 120sccm, the power is 1000W, the temperature and pressure are normal, and the clearing time is 5-10min.
[0089] Step 6.3, the etching gas is Ar, the gas flow rate is 120 sccm, the temperature and pressure are normal, and the RF power is 1200 W. The etching time is selected to be the time to etch 30% of the thickness of the top electrode to ensure that the top electrode is completely patterned and isolated, and the etching atmosphere and power will not etch the AlScN ferroelectric layer.
[0090] Step 7, remove the photoresist mask, the process is as follows:
[0091] Step 7.1, in an ultrasonic machine, use acetone organic solvent to clean the photoresist after dry etching, and the cleaning temperature is 60° C. The ultrasonic time depends on the power of the ultrasonic machine and the cleaning condition of the residual photoresist on the surface, and is usually 10-20 minutes.
[0092] In step 7.2, use isopropanol to remove the residual acetone solvent, and then use deionized water to remove the residual isopropanol solvent. Finally, use a nitrogen gun to blow dry the surface.
Claims
1. An aluminum-scandium-nitride ferroelectric capacitor memory based on a nitride bottom electrode, wherein the bottom electrode of the aluminum-scandium-nitride ferroelectric capacitor memory is a nitride bottom electrode.
2. The aluminum-scandium-nitride ferroelectric capacitor memory based on nitride bottom electrode according to claim 1, characterized in that: The aluminum-scandium-nitrogen ferroelectric capacitor memory is composed of a substrate, a nitride bottom electrode, an AlScN ferroelectric layer and a metal top electrode from bottom to top.
3. The aluminum-scandium-nitride ferroelectric capacitor memory based on nitride bottom electrode according to claim 2, characterized in that: The substrate is a heavily doped P-Si substrate, and the AlScN ferroelectric layer is Al 1-x Sc x N, 0.1≤x≤0.
3.
4. The aluminum-scandium-nitrogen ferroelectric capacitor memory based on a nitride bottom electrode according to claim 1, 2 or 3, characterized in that: The nitride bottom electrode is one of TiN, TaN, MoN, AgN and WN.
5. The method for preparing the aluminum-scandium-nitrogen ferroelectric capacitor memory based on the nitride bottom electrode according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, pre-treating the substrate; Step 2, depositing the nitride bottom electrode on the substrate in a nitrogen-rich environment, wherein the nitrogen-rich environment refers to a sputtering gas composed of nitrogen and argon with a flow ratio of 0.55 to 0.64; Step 3, depositing an AlScN ferroelectric layer on the nitride bottom electrode; Step 4: depositing a metal top electrode on the AlScN ferroelectric layer and processing the metal top electrode pattern.
6. The method for preparing the aluminum-scandium-nitrogen ferroelectric capacitor memory based on the nitride bottom electrode according to claim 5, characterized in that: The step 1, pre-treating the substrate includes cleaning and oxide removal, and the process is as follows: Step 1.1, using acetone, isopropanol, deionized water and ethanol to clean in sequence to remove impurities on the substrate surface; Step 1.2, using BOE solvent to remove oxides on the surface of the substrate at room temperature, and then using deionized water to remove residual BOE on the surface; the BOE solvent is a mixture of HF aqueous solution and NH4F aqueous solution.
7. The method for preparing the aluminum-scandium-nitrogen ferroelectric capacitor memory based on the nitride bottom electrode according to claim 5, characterized in that: The step 2 is to deposit the nitride bottom electrode on the substrate, and the process is as follows: Step 2.1, fixing the substrate; Step 2.2, using a metal target as a sputtering target and argon and nitrogen as sputtering gases, pre-sputtering the target to remove oxides on the surface of the target; Step 2.3, formal sputtering at room temperature.
8. The method for preparing the aluminum-scandium-nitrogen ferroelectric capacitor memory based on the nitride bottom electrode according to claim 7, characterized in that: In the step 2.2, the RF sputtering power is 400-500 W, the argon flow rate is 45-55 sccm, and the nitrogen flow rate is 25-35 sccm.
9. The method for preparing the aluminum-scandium-nitrogen ferroelectric capacitor memory based on the nitride bottom electrode according to claim 5, characterized in that: The step 3 is to deposit an AlScN ferroelectric layer on the nitride bottom electrode, and the process is as follows: Step 3.1, using the ScAl alloy target as the sputtering target, argon and nitrogen as the sputtering gas, pre-sputtering the target to remove the oxide on the surface of the target; wherein the RF sputtering power is 5-30kW, the flow rates of argon and nitrogen are 70-100sccm and 14-20sccm respectively, and the flow ratio of argon to nitrogen is 5:1; Step 3.2, formal sputtering at 100-300°C.
10. The method for preparing the aluminum-scandium-nitrogen ferroelectric capacitor memory based on the nitride bottom electrode according to claim 8, characterized in that: In step 4, a metal top electrode is deposited on the AlScN ferroelectric layer, and the process is as follows: Step 4.1, using a metal target as a sputtering target, argon and nitrogen as sputtering gases, pre-sputtering the target to remove oxides on the target surface, wherein the RF sputtering power is 400-500W; Step 4.2, formal sputtering at room temperature.